2016
DOI: 10.1111/cod.12679
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic components causing contact urticaria: a review and update

Abstract: Summary Immediate skin reactions are common in dermatological practice, but may often be overlooked. The main objective of this article is to provide an update of the literature concerning immediate‐type reactions or contact urticaria/contact urticaria syndrome caused by cosmetic ingredients in terms of immediate clinical symptoms, positive reactions following open, scratch or, most often, prick testing, and sometimes the detection of specific IgE antibodies. To this end, a selective search in different medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 144 publications
(99 reference statements)
0
32
0
3
Order By: Relevance
“…Likewise, purely lipid‐based vehicles can lead to an impaired skin barrier and facilitate deeper penetration of allergens into the skin. The same potential risk has to be observed for a number of natural – partly insufficiently purified – ingredients such as bisabolol, oat extract or lanolin when used in patients with damaged skin .…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, purely lipid‐based vehicles can lead to an impaired skin barrier and facilitate deeper penetration of allergens into the skin. The same potential risk has to be observed for a number of natural – partly insufficiently purified – ingredients such as bisabolol, oat extract or lanolin when used in patients with damaged skin .…”
Section: Discussionmentioning
confidence: 95%
“…Verhulst and Goossens recently published a review and update of cosmetic products that have been reported to produce contact urticaria. Causative agents cited included phenoxyethanol, polyaminopropyl biguanide, oxybenzone, menthol, and a number of plant‐derived ingredients including wheat and wheat protein hydrolyzates.…”
Section: Skin Reactivitymentioning
confidence: 99%
“…Skin sensitization is one of the principal concerns related to the use of cosmetics and is usually associated with fragrances, preservatives and hair dyes [21][22][23][24].…”
Section: Skin Sensitizationmentioning
confidence: 99%
“…Skin sensitization is one of the principal concerns related to the use of cosmetics and is usually associated with fragrances, preservatives and hair dyes [21][22][23][24]. Most studies have been done in vivo and a lower percentage on humans using the patch test method, to evaluate potential skin irritation caused by cosmetic ingredients (Figure 3).…”
Section: Skin Sensitizationmentioning
confidence: 99%